A National Survey of Computer Use in Rehabilitation Facilities. Research and Training Center Research Report - Blakemore, Thomas; Wisconsin Univ.-Stout, Menomonie. Stout Vocational Rehabilitation Inst. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
A survey of 3,581 rehabilitation facilities was conducted to determine their extent of computer use. Completed surveys were returned by 1,586 (44 percent) of the facilities, of which 864 (54 percent of the respondents) are using computers. The users indicated that computers are most frequently used for administrative purposes, whereas production and rehabilitation services uses are much less frequent. A number of statistical analyses were significant. It was found that the facilities that are currently using computers are much larger in terms of the number of clients they serve, the number of employees, and the size of their annual budgets. The users also provide a wider variety of rehabilitation services than the nonusers. Almost one-half of the current computer users own a microcomputer, one-quarter own a minicomputer, and only a few own a mainframe computer. There were sizeable differences in the costs of purchasing and operating these three classes of computers. However, there was no difference in terms of user satisfaction between the three classes of computer users. The results indicated that there is a substantial need for both customized software and for short-term training on how to use computers effectively in facilities. It was also found that the use and ownership of computers by facilities is likely to rise dramatically in the near future. Most of the facilities that will be acquiring a new computer system will be purchasing a microcomputer. (Author/KC)
Sponsoring Agency: National Inst. of Handicapped Research (ED), Washington, DC.
Contract Number: G008300117.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Oriented Programs; Computer Software; Computers; Disabilities; Institutions; Mental Retardation; Microcomputers; Minicomputers; Postsecondary Education; Rehabilitation Centers; Residential Schools; Sheltered Workshops; United States; Reports, Research